2012
DOI: 10.1103/physrevlett.109.115003
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Particle-Driven Alfvénic Modes in a Reversed Field Pinch

Abstract: Alfvénic modes are observed due to neutral beam injection for the first time in a reversed field pinch plasma. Modeling of the beam deposition and slowing down shows that the velocity and radial localization are high. This allows instability drive from inverse Landau damping of a bump-on-tail in the parallel distribution function or from free energy in the fast ion density gradient. Mode switching from a lower frequency toroidal mode number n=5 mode that scales with beam injection velocity to a higher frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Previously, it was shown that the n ¼ 4 frequency linearly depends on the Alfv en velocity but also remains well below the calculated n ¼ 4 TAE gap at 200-300 kHz. 13 In addition, earlier studies also revealed strong three-wave coupling among the n ¼ 5, n ¼ À1, and n ¼ 4 modes. The possibility that the n ¼ À1 mode is nonlinearly generated was speculated.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Previously, it was shown that the n ¼ 4 frequency linearly depends on the Alfv en velocity but also remains well below the calculated n ¼ 4 TAE gap at 200-300 kHz. 13 In addition, earlier studies also revealed strong three-wave coupling among the n ¼ 5, n ¼ À1, and n ¼ 4 modes. The possibility that the n ¼ À1 mode is nonlinearly generated was speculated.…”
Section: Resultsmentioning
confidence: 92%
“…4). Previous frequency-scaling studies revealed that the n ¼ 5 mode frequency shows some dependence on the beam ion velocity but weak dependence on the Alfv en velocity, 13 suggesting a non-eigenmode identity. To better examine the temporal dynamics, Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations